The Evolution of Regional Policy Objectives in Greece - Twenty Years of Regional Development Programmes - - Ilias Plaskovitis (European Regional Science Association (ERSA), 2006)
The Integrated Mediterranean Programmes of 1986-92 and the Regional Development Programmes implemented via the three Community Support Frameworks (CSFs) of the period 1989-2006, consist the best evidence of real, on-the-ground objectives and strategies followed by Greek regional policy-makers over the last twenty years. The proposed paper shall focus on the evolution of priorities, goals and modes of intervention exhibited by the above programmes during a period of great changes inside and outside the Greek economy. It will analyse the change in the relative weight of sectors, regions and social groups that occurs through successive planning exercises. It will compare such change with developments in the E.U., the Balkans, and Community policy priorities. Given that all 13 NUTS II Greek regions have been eligible under Objective 1 of E.U. structural funding throughout the above period, a total of 39 regional programmes have been designed and implemented under the 1st, 2nd and 3rd CSF for Greece. All of them have undergone different types of external evaluation (ex-ante, mid-term and ex-post) but nobody, to my knowledge, has attempted to compose their findings and outline overall trends with respect to their strategic objectives. Moreover to compare expressed objectives, derived from programme documents, with actual priorities, emerging from the phase of implementation through the concentration of resources and the relative weight of interventions. To examine potential conflicts both between programmes and within programmes, such as the degree of internal programme consistency as far as the different levels of objectives are concerned. It is finally worth examining the relationship between regional programme objectives and national policy priorities as the latter are expressed in the sectoral programmes also included in the CSFs of the above period. To what extent the former support national policy priorities and to what extent the latter serve the overriding goal of a more balanced regional development? In a last brief section the paper will attempt to draw conclusions that can be considered a useful contribution to the new programming framework for the 2007-13 period currently under preparation.
Keywords: 330